2005
DOI: 10.1063/1.1895486
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic reoxidation of microwave plasma-nitrided gate dielectrics

Abstract: The impact of nitrogen concentration on nitrided gate dielectric scaling has been found to depend on the process conditions used to incorporate nitrogen. For example, the variation in the nitrogen content of gate dielectrics processed at high pressure (>107Pa) has a strong impact on gate leakage current, but not on equivalent oxide thickness. While this effect allows nearly independent control of gate leakage and drive currents of the device, it prevents scaling of the gate dielectric. In contrast, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Indeed a number of candidate NMOS and PMOS metals have recently appeared. For NMOS, TaC x (4.2 eV) and TaTb x N (4.23 eV) appear promising [240,241], while for PMOS Ru (5.03 eV) and (Ta,Al)N with WF of 5.0 eV are suitable [242,243].…”
Section: Effective Work Functionsmentioning
confidence: 99%
“…Indeed a number of candidate NMOS and PMOS metals have recently appeared. For NMOS, TaC x (4.2 eV) and TaTb x N (4.23 eV) appear promising [240,241], while for PMOS Ru (5.03 eV) and (Ta,Al)N with WF of 5.0 eV are suitable [242,243].…”
Section: Effective Work Functionsmentioning
confidence: 99%
“…The incorporation of nitrogen has been extensively studied in gate dielectric films including SiO 2 and various high-k films because it plays a key role in present and near-future metaloxide-semiconductor devices. [4][5][6] Although N incorporation is a very promising process for control of interfacial reactions and enhancement of thermal stability of the film, the amount of nitrogen incorporated in HfO 2 is not stably maintained, which critically affects electrical device features. 4,7 Among the electrical device features, the most important characteristics in leakage and reliability of the gate dielectric are basically dependent on the band gap of the film and on band alignment with the Si substrate.…”
mentioning
confidence: 99%
“…It has been reported that the change in the nitrogen content of SiON gate dielectrics processed at high plasma pressure impacts gate leakage current, but not EOT. 12 The electrical performance in Fig. 8 can be explained by the nitrogen profile (inset) and by the way in which residual oxygen atoms and radicals behave during the nitridation process.…”
Section: Plasma Nitridation Optimizationmentioning
confidence: 99%